New interchange : English for international communication. Student's and Workbook 3 - Richards, Jack C; Hull, Jonathan; Proctor, Susan (Tp.HCM : Đại học Quốc gia Tp.HCM, 2000)
Sách hướng dẫn học tiếng Anh trong giao tiếp quốc tế.
Keywords: Anh ngữ; English language; Interchange; Tiếng Anh giao tiếp; English language -- Study and teaching